Thinking Rhetorically Writing for Professional and Public Audiences - Department of Writing Studies, Rhetoric, and Composition, Roger Williams University (Open textbook library., 2023)
Thinking Rhetorically: Writing in Professional and Public Contexts is dedicated to introducing students to a lifelong commitment of engaging with these problems that matter. As an academic discipline, Writing Studies’ contribution to engaging with problems can be applied to all areas of study and to all types of problems because we focus on the way language itself—discourse—is created and exchanged in the service of engaging problems. Writing Studies deepens students’ rhetorical awareness of how the ongoing conversations between groups of people shape and express the problems that matter.